Kadın ve Doğa Üzerindeki Tahakküme Alternatif bir Bakış: Ekofeminizm Üzerine bir Değerlendirme - Gezgin, Elif (Border Crossing, 2017)
Türkiye’de ve dünya genelinde yaşanan çevresel ve toplumsal sorunların yadsınamaz düzeye ulaştığı bir çağa tanıklık etmekteyiz. Bu çağın tarihsel arka planına bakıldığında, onun en temel özelliklerinden birinin, sınırları Batılı, eril, burjuva gibi niteliklerle belirlenmiş bir kurucu öznenin, kendisi dışında kalan ve onun karşıtı olarak konumlanan ‘öteki’ unsurlara yönelik tahakkümü olduğu görülür. Bu tahakküm kadın, doğa, azınlıklar ve diğer tüm ötekileştirilenler üzerindeki hakimiyetini yüzyıllardır sürdürmek adına her birine telafisi son derece güç düzeyde zarar vermektedir. Kadına yönelik şiddet her geçen gün daha fazla artmakta, doğa üzerindeki tahribat ise geri dönüşü olmayacak boyutlara ulaşmaktadır. Bu tahakküm; doğanın ve onunla özdeşleştirilen kadının, insanın (esasen erkeğin) hizmetine sunulmuş köleler olarak algılanmasına neden olan indirgemeci ve düalist tarihsel kabullerin izlerini taşımaktadır. Söz konusu kabullerin halen hüküm sürdüğü günümüzde, konunun sosyal bilimler alanında ele alınmasının önem taşıdığı düşünülmektedir. Bu çerçevede bu metinde, konuyu kadın ve doğa üzerindeki eşanlı tahakküme odaklanarak ve tahakküm sorununa bu iki ana problemi de aşan bir kapsayıcılıkta yer açarak irdeleyen ekofeminist yaklaşımın bazı temel izleklerine değinilmesi, bu yolla hakkında yeterli Türkçe kaynağın bulunmadığı ekofeminist araştırma alanının tanıtımına katkı sağlanması amaçlanmaktadır. ABSTRACT IN ENGLISH An Alternative Approach to Domination on Women and on the Environment: An Overview of Ecofeminism In Turkey and all around the world, we witness an era in which environmental and social problems have reached to an undeniable level. Considering the historical background of this era, it is seen that one of the main features of it is the constant presence of domination on the others different from the constituent subject characterized by qualities / features like Western, masculine, bourgeois and on the ones whose identities are socially constructed against this subject. This domination has been damaging women, the environment, minorities and all other marginalized groups in an irrecoverable way in order to keep his power. Violence against women has been increasing day by day and devastation on the environment has been reaching to an irreversible point. This domination carries the traces of reductive and dualistic historical acceptances which lead to the misperception of the environment and women -mostly identified with the environment- as slaves who have been put at the disposal of human (men in fact). In today’s world which these acceptances linger, it is thought that to handle this problem in social science is of capital importance. Within this framework, some basic ways which ecofeminist perspective follows will be touched upon. This perspective especially focuses on the simultaneous domination on women and the environment and takes the domination problem in an inclusive way exceeding these two main problems. In this paper, it is specifically aimed to present an overview, in Turkish, on the historical depredation of women and of the environment within the framework of its relationship with the issue of domination and dualistic viewpoints reinforcing this domination so as to contribute to the introduction of the ecofeminist approach about which there are few Turkish sources.